Efeito do tamanho e incentivos sobre a performance dos fundos de investimento em ações - Alves, Oreniva Patricia dos Santos (2021)
In the universe of the financial market, investment funds have gained notoriety in recent years in Brazil, with the expressive growth in the number of investors. In this sense, analyzing stock investment funds, checking their characteristics, and evaluating the impact of their size, as well as their performance rates, are essential for a healthy management, with positive returns. This paper discusses the identification of the characteristics of stock investment funds that can affect profitability and performance, helping the managers of these funds to make an optimal portfolio choice. Regarding the methodological aspects, the descriptive methodology was used, with the format of an empirical study and a quantitative approach. Two measures of excess return were used: the market-adjusted return model and the Capital Asset Pricing Model (CAPM), where time series regressions were estimated, and their results were used as dependent variables in the model created for analysis. The research was based on the study of a database of 334 actively managed stock funds, i.e., the manager seeks returns above the benchmark index, between the years of 2006 to 2018. As for the results, the research showed that: the investment funds that have differentiation between management and administration, generate specialization gains and result in better productivity; in relation to fund time, as it increases, the fund performance decreases; and performance-based incentives do not generate market returns for actively managed equity funds.